Identity on the borderland. Romance population of Eastern Serbia - Nowicka, Ewa (Balcanica Posnaniensia. Acta et studia, 2019)
The article concentrates on the analysis of ethnic identity of two romance groups living on the territory of Eastern Serbia: Vlachs and Cincars Aromanians).This area is a borderland, culturally, linguistically and politically; the situation significantly influences the ethnic identity choices of the two studied groups. The article is based on the data collected during three field studies: in 2015, 2016 and 2017. The author analyses in-depth interviews with Vlachs and Cincars, active in ethnic organizations and movements. Both aspects of the identity: psychological and behavioural are investigated, on one hand these aspects find expression in utterances, and on the other hand in behaviours and activities of both studied groups.